2022
DOI: 10.1111/1759-7714.14410
|View full text |Cite
|
Sign up to set email alerts
|

Elevated BTG2 improves the radiosensitivity of non‐small cell lung cancer (NSCLC) through apoptosis

Abstract: Background To identify radio‐responsive genes and explore the biological function of encoded proteins in non‐small cell lung cancer (NSCLC). Methods Radio‐responsive genes in irradiated H460 cells were screened from microarray data deposited in the Gene Expression Omnibus (GEO) database. A quantitative real time polymerase chain reaction assay was used to detect the expression of candidate radio‐responsive genes in irradiated cells. CCK‐8 assay, EDU assay, clone formation assay, immunofluorescence and flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…BTG2 can inhibit tumor growth and progression in breast cancer by suppressing the tumor microenvironments by regulating the mTORc2-AKT1-NFAT1-PHLPP2 signaling cascade [ 63 ]. In non-small cell lung cancer, BTG2 is a promising target for increasing radiation sensitivity with increased apoptosis and may be an early prognostic gene [ 64 ]. In transcriptomic analysis of mouse pancreatic tumor tissue, we identified BTG2 as a tumor suppressor gene whose expression was significantly induced by treatment with both T1-44 and Vactosertib in a mouse pancreatic tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…BTG2 can inhibit tumor growth and progression in breast cancer by suppressing the tumor microenvironments by regulating the mTORc2-AKT1-NFAT1-PHLPP2 signaling cascade [ 63 ]. In non-small cell lung cancer, BTG2 is a promising target for increasing radiation sensitivity with increased apoptosis and may be an early prognostic gene [ 64 ]. In transcriptomic analysis of mouse pancreatic tumor tissue, we identified BTG2 as a tumor suppressor gene whose expression was significantly induced by treatment with both T1-44 and Vactosertib in a mouse pancreatic tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…And the DNA repair agent AV-153 plays an important role in DNA repair [26]. It has been shown that overexpression of BTG2 in lung cancer cells leads to an increase in the number of DDR-inducedc-H2AX lesions [27]. However, the efect of VRK1 on DDR has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression can be activated by P53, leading to the inhibition of the cell cycle process [19]. In addition, BTG2 was also involved in many biological processes such as cell senescence [20], cell differentiation [21], oxidative damage [22] and DNA damage repair [23]. Then, what role does BTG2 play in the muscles?…”
Section: Introductionmentioning
confidence: 99%